Clinical impact of HSD3B1 polymorphism by metastatic volume and somatic HSD3B1 alterations in advanced prostate cancer. (8th November 2021) - Shiota, Masaki; Fujimoto, Naohiro; Sekino, Yohei; Tsukahara, Shigehiro; Nagakawa, Shohei; Takamatsu, Dai; Abe, Tatsuro; Kinoshita, Fumio; Ueda, Shohei; Ushijima, Miho; Matsumoto, Takashi; Kashiwagi, Eiji; et al.
Abstract: This study aimed to investigate the significance of HSD3B1 gene status including germline polymorphism and somatic alterations in prostate cancer. Patients with prostate cancer treated with androgen‐deprivation therapy, as well as tissues from metastatic prostate cancer, were included. Genomic DNA was extracted from cancer tissues and whole blood samples, and HSD3B1 (rs1047303, 1245C) was genotyped by Sanger sequencing. The association of HSD3B1 genotype with progression‐free survival according to metastatic volume was examined. Copy number alteration and gene expression of HSD3B1 were examined in prostate cancer cells and public datasets. Among 194 patients, 121 and 73 patients were categorized into low‐ and high‐volume diseases respectively. In multivariate analysis, the adrenal‐permissive genotype (AC/CC) was significantly associated with increased risk of progression compared with the adrenal‐restrictive genotype (AA) in low volume, but not high‐volume diseases. Somatic mutation in HSD3B1 was detected at least in two cases of castration‐resistant prostate cancer tissues. HSD3B1 amplification and overexpression were detected in castration‐resistant prostate cancer cells and tissues. The current findings suggest that both germline and somatic alterations of HSD3B1 may cooperatively promote castration resistance in prostate cancer and HSD3B1 as a promising biomarker for precision medicine, warranting further investigations.